2009
DOI: 10.1002/bit.22368
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of liquid–solid circulating fluidized bed ion exchange system for continuous protein recovery

Abstract: Liquid-solid circulating fluidized bed (LSCFB) is an integrated two-column (downcomer and riser) system which can accommodate two separate processes (adsorption and desorption) in the same unit with continuous circulation of the solid particles between the two columns. In this study, a mathematical model based on the assumption of homogeneous fluidization was developed considering hydrodynamics, adsorption-desorption kinetics and liquid-solid mass transfer. The simulation results showed good agreement with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…For simulation of the LSCFB ion-exchange system, a mathematical model considering both the hydrodynamics and the mass transfer was developed in our earlier study (Mazumder et al, 2009). The model is based on plug flow assumption, while internal and external diffusion were lumped in a rate co-efficient.…”
Section: Modeling and Simulation Of Lscfb Ion-exchange Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…For simulation of the LSCFB ion-exchange system, a mathematical model considering both the hydrodynamics and the mass transfer was developed in our earlier study (Mazumder et al, 2009). The model is based on plug flow assumption, while internal and external diffusion were lumped in a rate co-efficient.…”
Section: Modeling and Simulation Of Lscfb Ion-exchange Systemmentioning
confidence: 99%
“…Details of the mathematical model as well as the effect of various operating parameters on the performance of adsorption and desorption in the LSCFB are not reported here for brevity. Complete details are available in Mazumder et al (2009). However, for completeness, the governing equations for the downcomer and the riser, the parameters used, design and operating conditions of the LSCFB ionexchange system are summarized in Appendix A.…”
Section: Modeling and Simulation Of Lscfb Ion-exchange Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies on ion exchange process modeling can be categorized into three groups: 1) exploring novel numerical methods or appropriate reactor models (Kaczmarski et al, 1997;Koh et al, 1995;Slizneva and Natareev, 2004). For example, Kaczmarski et al (1997) developed an orthogonal collocation method based on moving finite elements for simulating ion exchange in fixed-bed; Koh et al (1995) tried to model the IX process of phenylalanine in fluidized beds using a completely mixed flow reactor (CMFR)-based model and a packed bed model and found the packed bed model had a better performance; 2) improving reactor configurations (Hwang and Lu, 1995;Boyer et al, 2008Boyer et al, , 2010Mazumder et al, 2009). For example, Hwang and Lu (1995) compared the performance of the semifluidized bed, the fluidized bed, and the packed bed by numerical simulations and concluded that the semi-fluidized bed has the highest treatment efficiency; Boyer et al (2008Boyer et al ( , 2010 developed process models for the ion exchange in a CMFR configuration for water treatment; 3) applications to different industries such as heavy metals removal (Menoud et al, 1998;Juang et al, 2003), high purity water production (Jia and Foutch, 2004;Hokanson, 2004), metal separation in elution process (Fatemi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, no intra-particle diffusion was considered in the models and the results predicted by the regeneration model were not in alignment with the experimental data. Mazumder et al (2009) developed an integrated model for the LiquideSolid Circulating Fluidized Bed (Lan et al, 2002) in which IX and resin regeneration operates simultaneously in continuous mode. However this model cannot be applied to the commonly used configurations (i.e.…”
Section: Introductionmentioning
confidence: 99%